Spa Diversity among MRSA and MSSA Strains of Staphylococcus aureus in North of Iran - Fatemeh Shakeri; Abolfath Shojai; Masoud Golalipour; Somaye Rahimi Alang; Hamid Vaez; Ezzat Allah Ghaemi (International Journal of Microbiology)
Protein A of Staphylococcus aureus is a pathogenic factor whose encoding gene, spa, shows a variation in length in different strains. In this study the spa gene variation in S. aureus isolated from healthy carriers and patients was studied, We also compared this variation among MRSA with MSSA strains. 208 strains of Staphylococcus aureus which we were isolated from Gorgan, north of Iran were studied, 121 cases from patients and 87 cases from healthy carriers, 59 out of them were MRSA and 149 MSSA. Samples DNA were extracted and amplified by specific primer of spa gene. In 4 (3.8%) strains of them no spa gene was detected, and 10.6% had a dual band (1200 and 1400 bp). In strains with one band, the length of spa gene differed from 1150 to 1500 bp. The most prevalent length was 1350–1400 bp (37%). The frequencies of short spa bands (1150–1200 bp) in patients strains were significantly higher. In 4 (3.8%) strains of them no spa gene was detected, and 10.6% had a dual band (1200 and 1400 bp). In strains with one band, the length of spa gene differed from 1150 to 1500 bp. The most prevalent length was 1350–1400 bp (37%). The frequencies of short spa bands (1150–1200 bp) in patients strains were significantly higher. The spa gene length of 1350–1400 bp in MSSA was more than in MRSA strains (P<.05). The average length of spa in isolated strains from urinary tract infections was more than others. It is concluded that the length of spa gene depends either on resistance to Methicillin or the source of S. aureus isolation.